PENGARUH NILAI TAKSIRAN DAN BIAYA IJARAH TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH PRODUK RAHN PADA PT. PEGADAIAN SYARIAH - Nurliza Lubis; Ainul Yusna Harahap; Agustina Nurul Fajriah (Bisnis-Net, 2023)
The research was conducted with the aim of determining the effect of the estimated value and cost of ijarah on customer decisions in choosing rahn products at PT Pegadaian Syariah. This type of research is quantitative, the source of data used is primary data. The pollulation and sample of this study were rahn customers at Pegadaian Sungai Liput which amounted to 1,949 and a sample of 96 respondents calculated based on the slovin formula. The data obtained were analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation models analyzed are multiple linear regression analysis, classical assumption test and hypothesis testing (T Test, F Test and Coefficient of Determination (R2). The results showed that partially the estimated value and cost of ijarah had a significant positive effect on the customer's decision in choosing rahn products. Simultaneously, all independent variables, namely estimated value and ijarah cost, together have a significant positive influence on the customer's decision in choosing rahn products.